Inquiry and industry inspired laboratories: the impact on students' perceptions of skill development and engagements. Issue 2 (9th March 2018) - George-Williams, Stephen R.; Soo, Jue T.; Ziebell, Angela L.; Thompson, Christopher D.; Overton, Tina L.
Abstract : Many examples exist in the chemical education literature of individual experiments, whole courses or even entire year levels that have been completely renewed under the tenets of context-based, inquiry-based or problem-based learning. The benefits of these changes are well documented and include higher student engagement, broader skill development and better perceived preparation for the workforce. However, no examples appear to have been reported in which an entire school's teaching laboratory programme has been significantly redesigned with these concepts in mind. Transforming Laboratory Learning (TLL) is a programme at Monash University that sought to incorporate industry inspired context-based, inquiry-based and problem-based learning into all the laboratory components of the School of Chemistry. One of the ways in which the effect of the programme was evaluated was through the use of an exit survey delivered to students at the completion of seven experiments that existed before the TLL programme as well as seven that were generated directly by the TLL programme. The survey consisted of 27 closed questions alongside three open questions. Overall, students found the new experiments more challenging but recognised that they were more contextualised and that they allowed students to make decisions. The students noted the lack of detailed guidance in the new laboratory manuals but raised the challenge, context and opportunity to undertake experimental design as reasons for enjoying the new experiments. Students' perceptions of their skill development shifted to reflect skills associated with experimental design when undertaking the more investigation driven experiments. These results are consistent with other literature and indicate the large scale potential success of the TLL programme, which is potentially developing graduates who are better prepared for the modern workforce.